The status of MRI databases across the world focused on psychiatric and neurological disorders - Tanaka, Saori C.; Kasai, Kiyoto; Okamoto, Yasumasa; Koike, Shinsuke; Hayashi, Takuya; Yamashita, Ayumu; Yamashita, Okito; Johnstone, Tom; Pestilli, Franco; Doya, Kenji; Okada, Go; Shinzato, Hotaka; et al. (Psychiatry and Clinical Neurosciences, 2024)
Neuroimaging databases for neuro‐psychiatric disorders enable researchers to implement data‐driven research approaches by providing access to rich data that can be used to study disease, build and validate machine learning models, and even redefine disease spectra. The importance of sharing large, multi‐center, multi‐disorder databases has gradually been recognized in order to truly translate brain imaging knowledge into real‐world clinical practice. Here, we review MRI databases that share data globally to serve multiple psychiatric or neurological disorders. We found 42 datasets consisting of 23,293 samples from patients with psychiatry and neurological disorders and healthy controls; 1245 samples from mood disorders (major depressive disorder and bipolar disorder), 2015 samples from developmental disorders (autism spectrum disorder, attention‐deficit hyperactivity disorder), 675 samples from schizophrenia, 1194 samples from Parkinson's disease, 5865 samples from dementia (including Alzheimer's disease), We recognize that large, multi‐center databases should include governance processes that allow data to be shared across national boundaries. Addressing technical and regulatory issues of existing databases can lead to better design and implementation and improve data access for the research community. The current trend toward the development of shareable MRI databases will contribute to a better understanding of the pathophysiology, diagnosis and assessment, and development of early interventions for neuropsychiatric disorders.